Mencari Makna Pembangunan Sosial: Studi Kasus Sektor Informal di Kota Solo - Wirutomo, Paulus (Masyarakat: Jurnal Sosiologi, 2013)
The present development concept has been widely criticized for being too sectoral and growth oriented. A new concept like Human Development introduced by the United Nation is a good alternative, but it is still sectoral in nature. This article tries to offer a more sociological concept of development, since it is based on the contention that to develop human being we have to develop its society. It means to develop “the basic elements of socio-cultural life” namely: the structural, cultural and processual elements. By analyzing the data on the informal sector in Solo collected with SSM methodology, I have come to the conclusion that the government of Solo city has been to some degree practicing the social development concept through developing the structural, cultural and processual aspects leading to the more inclusive society.